Vaccination in persons with systemic lupus erythematosus: the current state of the problem - B. S. Belov; T. V. Popkova; G. M. Tarasova; N. V. Muravieva (Современная ревматология, 2022)
Vaccination plays an important role in the prevention of infectious diseases in patients with immunoinflammatory diseases. When vaccinating patients with systemic lupus erythematosus (SLE), as with other immunoinflammatory rheumatic diseases, its safety is of great importance, including mitigating the risks of the primary disease or the development of new autoimmune phenomena. Many practitioners continue to consider autoimmune diseases as a contraindication for vaccination due to the perceived possibility of their exacerbation and reduced vaccine effectiveness during active immunosuppressive therapy.The lecture presents current data on the immunogenicity, efficacy and safety of vaccines against a number of infections caused by influenza viruses, hepatitis B, Herpes zoster, human papilloma viruses, COVID-19 and pneumococcus in patients with SLE. It has been shown that the benefits of vaccination in patients with SLE significantly outweigh the risk of adverse events or exacerbations of the disease. At the same time, it was noted that the problem of vaccination of such patients requires further study.